Polishing composition, polishing method, and method of manufacturing semiconductor substrate

KR103018408B1Active Publication Date: 2026-09-11FUJIMI INCORPORATED
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
KR1020230016636
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-02-08
Publication Date
2026-09-11
Estimated Expiration
2043-02-08

Smart Images

  • Figure 112023014650139-PAT00001
    Figure 112023014650139-PAT00001
  • Figure 112023014650139-PAT00002
    Figure 112023014650139-PAT00002
  • Figure 112023014650139-PAT00003
    Figure 112023014650139-PAT00003
Patent Text Reader

Abstract

A means for improving the ratio of the polishing rate of SiOC to the polishing rate of SiN is provided. A polishing composition is provided comprising abrasive particles comprising at least one type of zirconia particle, at least one salt comprising a monovalent anion and a monovalent or higher cation, a selectivity improver that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, and a pH adjuster comprising at least one type of acid, wherein the pH is greater than 3.0 and less than 7.0, and the zeta potential of the abrasive particles is a positive value.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polishing composition, a polishing method, and a method for manufacturing a semiconductor substrate. Background Technology

[0002] In recent years, new microfabrication technologies are being developed in response to the increasing integration and performance of Large Scale Integration (LSI). Chemical mechanical polishing (CMP) is one such method and is a technology frequently used in LSI manufacturing processes, particularly in the planarization of interlayer insulating films, metal plug formation, and damascene wiring formation during the multilayer wiring formation process.

[0003] Low-dielectric constant (Low-k) materials are used as interlayer insulating film materials in the multilayer wiring formation process to suppress inter-wire capacitance. SiOC (carbon-doped silicon oxide, which is SiO2 doped with C, is also referred to as carbon-containing silicon oxide) formed by the plasma CVD method is widely used as a low-dielectric constant (Low-k) material.

[0004] As a technique for polishing SiOC, Japanese Patent Publication No. 2017-139349 discloses a polishing composition containing cerium-containing abrasive particles and hydroxyalkylcellulose, having a pH of 6.0 or higher. According to Japanese Patent Publication No. 2017-139349, the polishing speed of SiOC can be improved by using such a composition. The problem to be solved

[0005] Recently, substrates containing both SiOC and SiN (silicon nitride) have come into use, and there has been an increasing demand to selectively polish SiOC on such substrates. However, according to the polishing composition disclosed in Japanese Patent Publication No. 2017-139349, there was a problem in that the ratio of the polishing speed of SiOC to the polishing speed of SiN (selectivity ratio) was low.

[0006] Therefore, the present invention aims to provide a means to improve the ratio of the polishing rate of SiOC to the polishing rate of SiN.

[0007] The inventors of the present invention conducted a thorough investigation to solve the above problem. As a result, they discovered that the problem is solved by controlling the pH and the zeta potential of the abrasive particles to within a specific range in a polishing composition comprising zirconia particles (abrasive particles), a salt (selectivity enhancer) composed of a monovalent anion and a cation of monovalent or higher, and an acid (pH adjuster), and thus completed the present invention.

[0008] That is, one embodiment of the present invention is a polishing composition comprising abrasive particles comprising at least one type of zirconia particle, a selectivity enhancer comprising at least one salt composed of a monovalent anion and a monovalent or higher cation that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, and a pH adjuster comprising at least one type of acid, wherein the pH is greater than 3.0 and less than 7.0, and the zeta potential of the abrasive particles is a positive value. Specific details for implementing the invention

[0009] Embodiments of the present invention are described below, but the technical scope of the present invention should be determined based on the description in the patent claims and is not limited to the following forms only.

[0010] In this specification, unless otherwise specified, operations and measurements of physical properties, etc. are performed under conditions of room temperature (20°C or higher and 25°C or lower) and relative humidity of 40% RH or higher and 50% RH or lower. Additionally, in this specification, the ratio of the polishing rate of SiOC to the polishing rate of SiN is simply referred to as the "selectivity ratio," and a selectivity ratio enhancer that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN is simply referred to as the "selectivity ratio enhancer." The embodiments described in this specification may be converted into other embodiments by arbitrarily combining them.

[0011] One embodiment of the present invention is a polishing composition comprising: abrasive particles comprising at least one type of zirconia particle; a selectivity enhancer comprising at least one salt composed of a monovalent anion and a monovalent or higher cation, which improves the ratio of the polishing rate of SiOC to the polishing rate of SiN; and a pH adjuster comprising at least one type of acid, wherein the pH is greater than 3.0 and less than 7.0, and the zeta potential of the abrasive particles is a positive value. By the above composition, the ratio of the polishing rate of SiOC to the polishing rate of SiN (selectivity ratio) can be improved.

[0012] The mechanism by which the above-mentioned effects are obtained is believed to be as follows. However, the following mechanism is merely speculative and does not limit the scope of the present invention.

[0013] Zirconia particles as abrasive particles can polish SiOC at high speed compared to silica particles, ceria particles, and alumina particles.

[0014] Salts composed of monovalent anions and cations of one or more valence, used as selectivity enhancers, have monovalent anions attached to the surface of abrasive particles containing zirconia particles, thereby lowering the hydrophilicity of the surface. Consequently, abrasive particles can more easily approach the surface of SiOC, which has high hydrophobicity, and thus the polishing speed of SiOC is improved. On the other hand, if a salt composed of divalent or higher anions and cations of one or more valence is used, anions attach to the abrasive particles, causing the zeta potential of the abrasive particles to become negative (-), which may cause the abrasive particles to repel the negatively charged surface of SiOC. As a result, there is a concern that the polishing speed of SiOC may decrease, and a sufficient selectivity ratio may not be obtained.

[0015] As described above, the acid acting as a pH adjuster causes anions to attach to the surface of abrasive particles containing zirconia particles, thereby lowering the hydrophilicity of the surface. Consequently, the abrasive particles become more accessible to the surface of the SiOC, which has high hydrophobicity, thereby improving the polishing speed of the SiOC. Additionally, the pH of the polishing composition is controlled to be greater than 3.0 and less than 7.0 by the pH adjuster. If the pH is within the above range, a sufficient effect of improving selectivity is obtained. On the other hand, if the pH is 3.0 or lower, the surface of the SiOC becomes positively charged (+) and repels the abrasive particles having a positive (+) zeta potential, which may cause the polishing speed of the SiOC to decrease. If the pH is 7.0 or higher, the zeta potential of the abrasive particles containing zirconia particles becomes near zero (0), reducing the repulsion between the abrasive particles and potentially causing aggregation (also, the isoelectric point of zirconia particles is typically pH 7.0 to 9.0 (near 8.0)).

[0016] In addition, if the pH is within the range of greater than 3.0 and less than 7.0, the abrasive particles containing zirconia particles have a positive (+) zeta potential in the polishing composition, and the abrasive particles having a positive (+) zeta potential are attracted to the surface of the negatively charged SiOC, thereby improving the polishing speed of SiOC.

[0017] Accordingly, by applying the polishing composition according to the present form to a polishing target containing SiOC and SiN, it becomes possible to polish SiOC at a high speed. As a result, it becomes possible to significantly improve the ratio of the polishing speed of SiOC to the polishing speed of SiN.

[0018] Hereinafter, a polishing composition relating to the present form will be described in detail.

[0019] [Object to be polished]

[0020] The object to be polished using the present type of polishing composition preferably comprises SiOC (carbon-added silicon oxide) and SiN (silicon nitride).

[0021] The material to be polished may include other materials other than SiOC and SiN. Examples of other materials include silicon oxide, single-crystal silicon, polycrystalline silicon (polysilicon), amorphous silicon, polycrystalline silicon doped with n-type or p-type impurities, amorphous silicon doped with n-type or p-type impurities, SiGe, elemental metals (e.g., tungsten, copper, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, osmium, etc.), metal nitrides (e.g., tantalum nitride (TaN), titanium nitride (TiN), etc.), and organic materials (e.g., amorphous carbon, spin-on carbon (SOC), diamond-like carbon (DLC), nanocrystalline diamond, graphene, etc.).

[0022] Films containing these materials can be formed by chemical vapor deposition (CVD), physical vapor deposition (PVD), spin coating, etc.

[0023] [Jilip]

[0024] The polishing composition according to the present form includes zirconia particles as abrasive particles. The zirconia particles have the function of mechanically polishing an object to be polished. Zirconia particles may be used in a single type or in a combination of two or more types. Furthermore, commercially available zirconia particles may be used, or synthetic products may be used. In addition, zirconia typically contains hafnia (HfO2), which is an unavoidable impurity. In this specification, numerical values ​​related to composition, such as content, are calculated by considering the unavoidable impurity hafnia (HfO2) as zirconia (ZrO2).

[0025] The zirconia particles are preferably colloidal zirconia particles or ground / fired zirconia particles, and are more preferably colloidal zirconia particles. Additionally, the zirconia particles may not be doped, or may be doped with, for example, yttrium (Y) or its oxide, calcium oxide, or magnesium oxide. Furthermore, the crystal structure of the zirconia particles is not particularly limited and may be monoclinic, tetragonal, or cubic.

[0026] The shape of the zirconia particles is not particularly limited and may be spherical or non-spherical. Examples of non-spherical shapes include polygonal prisms such as triangular or square prisms, cylindrical shapes, pillow shapes where the center of a cylinder is more convex than the ends, donut shapes where the center of a disc is penetrated, plate shapes, so-called cocoon shapes with a constriction in the center, so-called associative spherical shapes where multiple particles are integrated, so-called star candy shapes with multiple protrusions on the surface, rod shapes, rhombus shapes, angular shapes, rugby ball shapes, etc., and are not particularly limited.

[0027] Zirconia particles are aggregates comprising primary particles and / or secondary particles. The aggregates may be formed from a combination of individual particles, which are known in the art as primary particles, while the aggregated combination of particles is known in the art as secondary particles. The zirconia particles in the polishing composition may be in the form of primary particles or in the form of secondary particles which are aggregates of primary particles. Alternatively, the zirconia particles may exist in both the form of primary particles and secondary particles. In a preferred embodiment, the zirconia particles are present in the polishing composition at least partially in the form of secondary particles.

[0028] The particle diameter of the zirconia particles according to the present embodiment is preferably 5 nm or more and 200 nm or less, more preferably 10 nm or more and 150 nm or less, even more preferably 30 nm or more and 100 nm or less, and particularly preferably 50 nm or more and 90 nm or less. If the particle diameter of the zirconia particles is 5 nm or more, polishing becomes efficient and a sufficient polishing speed is obtained. If the particle diameter of the zirconia particles is 200 nm or less, the dispersion stability of the polishing composition is excellent. Furthermore, in this specification, the particle diameter of the zirconia particles refers to the particle diameter (D50, hereinafter also simply referred to as "D50") at which the integrated particle volume on the fine particle side reaches 50% of the total particle volume in the particle size distribution obtained by the laser diffraction scattering method. The D50 of the zirconia particles in this specification adopts the value measured by the method described in the examples.

[0029] In the present embodiment, one of the features is that the abrasive particles (preferably zirconia particles) in the polishing composition have a positive zeta potential. Accordingly, the abrasive particles having a positive (+) zeta potential are attracted to the surface of the negatively (-) charged SiOC, thereby improving the polishing speed of the SiOC. The zeta potential of the abrasive particles (preferably zirconia particles) in the polishing composition is preferably greater than 0 mV and less than or equal to +70 mV, more preferably greater than or equal to +10 mV and less than or equal to +60 mV, even more preferably greater than or equal to +20 mV and less than or equal to +50 mV, and particularly preferably greater than or equal to +30 mV and less than or equal to +45 mV. If the zeta potential of the abrasive particles (preferably zirconia particles) in the polishing composition is greater than or equal to +10 mV, the force attracting the abrasive particles (preferably zirconia particles) to the surface of the negatively (-) charged SiOC increases, so polishing becomes even more efficient. If the zeta potential of abrasive particles (preferably zirconia particles) in the polishing composition is +70 mV or less, the removal of the abrasive particles is facilitated by washing after polishing. The zeta potential of the abrasive particles in the polishing composition can be controlled by the type or amount of pH adjusters or selectivity enhancers in the polishing composition. Furthermore, the zeta potential of the abrasive particles in this specification adopts the value measured by the method described in the examples.

[0030] The content (concentration) of abrasive particles (preferably zirconia particles) in the polishing composition is not particularly limited. In the case of a polishing composition used as a polishing liquid for polishing an object to be polished (typically a slurry-type polishing liquid, which may also be referred to as a working slurry or a polishing slurry), the content of abrasive particles is preferably 0.01 mass% or more and 10.0 mass% or less with respect to the total mass of the polishing composition, more preferably 0.01 mass% or more and 5.0 mass% or less, even more preferably 0.01 mass% or more and 1.0 mass% or less, even more preferably 0.05 mass% or more and 1.0 mass% or less, particularly preferably 0.06 mass% or more and 0.50 mass% or less, and most preferably 0.07 mass% or more and 0.30 mass% or less. If the content of abrasive particles is within the above range, a sufficient polishing rate against SiOC is obtained, and a polishing composition with excellent cost-effectiveness is obtained.

[0031] In addition, in the case of a polishing composition used for polishing after dilution (i.e., a concentrate, a raw material of a working slurry), the abrasive content is typically 30 mass% or less, and preferably 25 mass% or less, from the perspective of preservation stability or filterability. In addition, in the case of a polishing composition used for polishing after dilution to take advantage of the benefits of using a concentrate, the abrasive content is preferably 0.3 mass% or more, and more preferably 0.5 mass% or more.

[0032] In addition, if the abrasive composition contains two or more types of abrasive particles, the content of the abrasive particles is intended to be the total amount thereof.

[0033] The polishing composition according to the present form may further include abrasive particles other than zirconia particles, provided that the effects of the present invention are not impaired. Such other abrasive particles may be any of inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include, for instance, particles composed of unmodified silica, cationic modified silica, metal oxides such as alumina, ceria, and titania, silicon nitride particles, silicon carbide particles, boron nitride particles, etc. Specific examples of organic particles include, for instance, polymethyl methacrylate (PMMA) particles. Such other abrasive particles may be used individually or in combination of two or more types. Furthermore, such other abrasive particles may be commercially available products or synthetic products.

[0034] However, the content of the other abrasive particles is preferably 20 mass% or less with respect to the total mass of the abrasive particles, more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably 1 mass% or less. Most preferably, the content of the other abrasive particles is 0 mass%, that is, the abrasive particles consist only of zirconia particles.

[0035] [Selection Ratio Enhancer]

[0036] The polishing composition of the present form includes a selectivity enhancer that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN. The selectivity enhancer includes at least one salt composed of a monovalent anion and a cation with one or more valencies. The salt may be used alone or in combination of two or more types.

[0037] The anions constituting the salt must be monovalent. If anions with a valence of 2 or higher are used, the anions may attach to the abrasive grains, causing the zeta potential of the abrasive grains to become negative. As a result, the polishing speed of SiOC may decrease, and there is a concern that a sufficient selectivity ratio may not be obtained. As monovalent anions, halides such as fluoride ions, chloride ions, bromide ions, and iodide ions, nitrate ions, acetate ions, formate ions, propionic ions, butyrate ions, valerate ions, 2-methylbutyrate ions, n-hexanoate ions, 3,3-dimethylbutyrate ions, 2-ethylbutyrate ions, 4-methylpentanoate ions, n-heptanoate ions, 2-methylhexanoate ions, n-octanoate ions, 2-ethylhexanoate ions, benzoate ions, glycolate ions, salicylate ions, glycerinate ions, lactate ions, 2-furancarboxylate ions, 3-furancarboxylate ions, 2-tetrahydrofurancarboxylate ions, methoxyacetate ions, methoxyphenylacetate ions, phenoxyacetate ions, and methanesulfonate ions, Examples include ethanesulfonate ions and isethionate ions. Among these, nitrate ions and acetate ions are preferred from the perspective of further improving selectivity, and acetate ions are more preferred.

[0038] The valence of the cation constituting the salt is not particularly limited, such as monovalent, divalent, and trivalent. Examples of cations with a valence of monovalent or higher include sodium ions, potassium ions, lithium ions, calcium ions, magnesium ions, ammonium ions, etc. Among these, sodium ions, potassium ions, and ammonium ions are preferred from the perspective of further improving the selectivity ratio, and ammonium ions are more preferred.

[0039] Specific examples of salts include ammonium acetate, sodium acetate, potassium acetate, lithium acetate, magnesium acetate, calcium acetate, ammonium nitrate, sodium nitrate, potassium nitrate, lithium nitrate, magnesium nitrate, calcium nitrate, ammonium fluoride, sodium fluoride, potassium fluoride, lithium fluoride, magnesium fluoride, calcium fluoride, ammonium chloride, sodium chloride, potassium chloride, lithium chloride, magnesium chloride, calcium chloride, ammonium bromide, sodium bromide, potassium bromide, lithium bromide, magnesium bromide, calcium bromide, ammonium iodide, sodium iodide, potassium iodide, lithium iodide, magnesium iodide, calcium iodide, etc. Among these, from the perspective of further improving the selectivity ratio, ammonium acetate, sodium acetate, potassium acetate, and ammonium nitrate are preferred, ammonium acetate, sodium acetate, and potassium acetate are more preferred, and ammonium acetate is even more preferred. That is, according to a preferred embodiment of the present invention, the selectivity ratio enhancer comprises ammonium acetate. According to a preferred embodiment of the present invention, the selectivity ratio enhancer consists solely of ammonium acetate.

[0040] The content (concentration) of the selectivity enhancer (preferably ammonium acetate) in the polishing composition is not particularly limited. In the case of a polishing composition used as a polishing liquid for polishing an object to be polished (typically a slurry-type polishing liquid, which may also be referred to as a working slurry or polishing slurry), the content (concentration) of the selectivity enhancer is, from the perspective of improving selectivity, preferably 30 ppm or more and 2000 ppm or less with respect to the total mass of the polishing composition, more preferably 50 ppm or more and 1000 ppm or less, even more preferably 75 ppm or more and 750 ppm or less, particularly preferably 100 ppm or more and 700 ppm or less, and most preferably 300 ppm or more and 600 ppm or less. If the content of the selectivity enhancer is within the above range, the selectivity can be further improved. In addition, in this specification, "ppm" means "mass ppm".

[0041] In addition, from the perspective of further improving the stability of the polishing composition, the content (concentration) of the selectivity improver (preferably ammonium acetate) is preferably 50 ppm or more and 500 ppm or less with respect to the total mass of the polishing composition, and more preferably 50 ppm or more and 200 ppm or less.

[0042] In addition, in the case of a polishing composition used for polishing after dilution (i.e., a concentrate, a raw material of a working slurry), the content (concentration) of a selectivity enhancer (preferably ammonium acetate) is typically 3 mass% (30,000 ppm) or less, and preferably 2 mass% (20,000 ppm) or less, from the perspective of storage stability or filterability. In addition, from the perspective of taking advantage of the benefits of using a concentrate, the content of the selectivity enhancer in the case of a polishing composition used for polishing after dilution is preferably 100 ppm or more, and more preferably 500 ppm or more.

[0043] In addition, if the polishing composition includes two or more selectivity enhancers, the content of the selectivity enhancers is intended to be the total amount thereof.

[0044] In addition, the ratio of the amount of selectivity improver to the amount of agglutinates (amount of selectivity improver / amount of agglutinates) (mass ratio) is preferably 0.01 or more and 5 or less, more preferably 0.05 or more and 1 or less, even more preferably 0.1 or more and 0.8 or less, and particularly preferably 0.3 or more and 0.7 or less. If the ratio of the amount of selectivity improver to the amount of agglutinates is within the above range, the selectivity can be further improved.

[0045] The polishing composition according to the present form may further include, as a selectivity enhancer, other substances other than the salt composed of the monovalent anion and monovalent or higher cations having the function of improving selectivity, within a range that does not impede the effects of the present invention. However, the content of said other substances is preferably 20 mass% or less with respect to the total mass of the selectivity enhancer, more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably 1 mass% or less. Most preferably, the content of the other substances is 0 mass%, that is, the selectivity enhancer is in a form consisting only of the salt composed of the monovalent anion and monovalent or higher cations.

[0046] [Dispersed Sales]

[0047] The abrasive composition of the present form preferably includes a dispersion medium for dispersing each component. Examples of dispersion media include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone; or mixtures thereof. Among these, water is preferred as the dispersion medium. That is, according to a preferred embodiment of the present invention, the dispersion medium comprises water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Furthermore, the term "substantially" above implies that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved; more specifically, it preferably consists of 90 mass% or more and 100 mass% or less of water and 0 mass% or more and 10 mass% or less of a dispersion medium other than water, and more preferably consists of 99 mass% or more and 100 mass% or less of water and 0 mass% or more and 1 mass% or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.

[0048] From the perspective of not hindering the action of the components included in the polishing composition, water that contains as few impurities as possible is preferred as the dispersion medium; specifically, pure water, ultrapure water, or distilled water that has had impurity ions removed using an ion exchange resin and then foreign substances removed through a filter is more preferable.

[0049] [pH and pH adjusters]

[0050] The polishing composition according to the present form has a pH greater than 3.0 and less than 7.0. If the pH is 3.0 or lower, as mentioned above, the polishing speed of SiOC is reduced, and there is a risk that the desired selectivity ratio cannot be obtained. If the pH is 7.0 or higher, aggregation of abrasive particles may occur as mentioned above.

[0051] The pH of the polishing composition is preferably 3.5 or higher and 6.5 or lower, more preferably 4.0 or higher and 6.0 or lower, and even more preferably 4.5 or higher and 5.5 or lower, from the viewpoint of improving selectivity. In addition, the pH of the polishing composition can be measured by a pH meter. The pH in this specification adopts the value measured by the method described in the examples.

[0052] The abrasive composition according to the present form comprises a pH adjusting agent. The pH adjusting agent comprises at least one acid. The acid may be either an inorganic acid or an organic acid. The acid may be used alone or in combination of two or more types.

[0053] Specific examples of inorganic acids include hydrochloric acid, hydrofluoric acid, nitric acid, etc. Specific examples of organic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glycerinic acid, lactic acid, 2-furancarboxylic acid, 3-furancarboxylic acid, 2-tetrahydrofurancarboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, phenoxyacetic acid, methanesulfonic acid, ethanesulfonic acid, isethionic acid, etc. Among these, nitric acid and acetic acid are preferred from the perspective of further improving selectivity, and acetic acid is more preferred. That is, according to a preferred embodiment of the present invention, the pH adjuster comprises acetic acid. According to a more preferred embodiment of the present invention, the pH adjuster consists solely of acetic acid.

[0054] The amount of pH adjuster added is not particularly limited, and it can be appropriately adjusted so that the abrasive composition reaches the desired pH.

[0055] In addition, a base may be used as a pH adjuster as needed, but according to a preferred embodiment of the present invention, the pH adjuster consists of at least one acid.

[0056] [Additives]

[0057] The polishing composition according to the present embodiment may further contain known additives that can be used in polishing compositions, such as dispersants, oxidizing agents, complexing agents, preservatives, and antifungal agents, to the extent that the effects of the present invention are not impaired. Since the polishing composition according to the present embodiment is acidic, it is preferable to include an antifungal agent. In addition, it is also a preferred embodiment to include a dispersant in order to improve the dispersion stability of abrasive particles (particularly zirconia particles). That is, in a preferred embodiment of the present invention, the polishing composition comprises abrasive particles comprising at least one type of zirconia particle, a selectivity enhancer comprising at least one salt consisting of a monovalent anion and a monovalent or higher cation that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, a pH adjuster comprising at least one type of acid, a dispersion medium, and at least one selected from the group consisting of an antifungal agent and a dispersant. In a more preferred embodiment of the present invention, the polishing composition is substantially composed of at least one abrasive particle comprising at least one zirconia particle, a selectivity enhancer comprising at least one salt consisting of a monovalent anion and a monovalent or higher cation that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, a pH adjuster comprising at least one acid, a dispersion medium, and at least one selected from the group consisting of an antifungal agent and a dispersant.Here, the phrase “the polishing composition is substantially composed of abrasive particles comprising at least one type of zirconia particle, a selectivity improver comprising at least one salt consisting of a monovalent anion and a cation of at least one valent or higher that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, a pH adjuster comprising at least one type of acid, a dispersion medium, and at least one selected from the group consisting of an antifungal agent and a dispersant” implies that the total content of the abrasive particles, the selectivity improver, the pH adjuster, the dispersion medium, and the antifungal agent and / or dispersant exceeds 99 mass% (upper limit: 100 mass%) with respect to the polishing composition. Preferably, the polishing composition consists of abrasive particles, a selectivity improver, a pH adjuster, a dispersion medium, and an antifungal agent and / or dispersant (total content = 100 mass%).

[0058] Antifungal agents (preservatives) are not particularly limited and can be appropriately selected according to the desired use and purpose. Specifically, examples include isothiazoline-based preservatives such as 1,2-benzisothiazol-3(2H)-one (BIT), 2-methyl-4-isothiazolin-3-one, and 5-chloro-2-methyl-4-isothiazolin-3-one, as well as phenoxyethanol.

[0059] Alternatively, the antifungal agent (preservative) may be a compound represented by the following chemical formula 1.

[0060]

[0061] In the above chemical formula 1, R 1 to R 5 Each is a substituent consisting of at least two atoms selected from the group consisting of hydrogen atoms or carbon atoms, hydrogen atoms, and oxygen atoms, each independently.

[0062] Examples of substituents composed of at least two atoms selected from the group consisting of carbon atoms, hydrogen atoms, and oxygen atoms include, for instance, a hydroxyl group, a carboxyl group having 1 to 20 carbon atoms, a hydroxyalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a hydroxyalkoxy group having 1 to 20 carbon atoms, an alkoxycarbonyl group having 2 to 21 carbon atoms, an aryl group having 6 to 30 carbon atoms, an aralkyl group (arylalkyl group) having 7 to 31 carbon atoms, an aryloxy group having 6 to 30 carbon atoms, an aryloxycarbonyl group having 7 to 31 carbon atoms, an aralkyloxycarbonyl group having 8 to 32 carbon atoms, an acyl group having 1 to 20 carbon atoms, an acyloxy group having 1 to 20 carbon atoms, etc.

[0063] More specifically, examples of alkyl groups having 1 to 20 carbon atoms include straight-chain alkyl groups such as methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups; branched alkyl groups such as isopropyl, isobutyl, s-butyl, t-butyl, t-amyl, neopentyl, 3-methylpentyl, 1,1-diethylpropyl, 1,1-dimethylbutyl, 1-methyl-1-propylbutyl, 1,1-dipropylbutyl, 1,1-dimethyl-2-methylpropyl, and 1-methyl-1-isopropyl-2-methylpropyl; Examples include cyclic alkyl groups such as cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, and norbornenyl groups.

[0064] Examples of hydroxyalkyl groups with 1 to 20 carbon atoms include hydroxymethyl, 2-hydroxyethyl, 2-hydroxy-n-propyl, 3-hydroxy-n-propyl, 2-hydroxy-n-butyl, 3-hydroxy-n-butyl, 4-hydroxy-n-butyl, 2-hydroxy-n-pentyl, 3-hydroxy-n-pentyl, 4-hydroxy-n-pentyl, 5-hydroxy-n-pentyl, 2-hydroxy-n-hexyl, 3-hydroxy-n-hexyl, 4-hydroxy-n-hexyl, 5-hydroxy-n-hexyl, 6-hydroxy-n-hexyl, etc.

[0065] Examples of alkoxy groups having 1 to 20 carbon atoms include straight-chain alkoxy groups such as methoxy, ethoxy, n-propyloxy, n-butyloxy, n-pentyloxy, n-hexyloxy, n-heptyloxy, n-octyloxy, n-nonyloxy, and n-decyloxy; branched alkoxy groups such as isopropyloxy, isobutyloxy, s-butyloxy, t-butyloxy, t-amyloxy, neopentyloxy, 3-methylpentyloxy, 1,1-diethylpropyloxy, 1,1-dimethylbutyloxy, 1-methyl-1-propylbutyloxy, 1,1-dipropylbutyloxy, 1,1-dimethyl-2-methylpropyloxy, and 1-methyl-1-isopropyl-2-methylpropyloxy; Examples include cyclic alkoxy groups such as cyclobutyloxy, cyclopentyloxy, cyclohexyloxy, cycloheptyloxy, cyclooctyloxy, and norbornenyloxy.

[0066] Examples of hydroxyalkoxy groups having 1 to 20 carbon atoms include hydroxymethoxy group, 2-hydroxyethoxy group, 2-hydroxy-n-propyloxy group, 3-hydroxy-n-propyloxy group, 2-hydroxy-n-butyloxy group, 3-hydroxy-n-butyloxy group, 4-hydroxy-n-butyloxy group, 2-hydroxy-n-pentyloxy group, 3-hydroxy-n-pentyloxy group, 4-hydroxy-n-pentyloxy group, 5-hydroxy-n-pentyloxy group, 2-hydroxy-n-hexyloxy group, 3-hydroxy-n-hexyloxy group, 4-hydroxy-n-hexyloxy group, 5-hydroxy-n-hexyloxy group, 6-hydroxy-n-hexyloxy group, etc. It is possible.

[0067] Examples of alkoxycarbonyl groups having 2 to 21 carbon atoms include methoxycarbonyl groups, ethoxycarbonyl groups, propoxycarbonyl groups, butoxycarbonyl groups, pentyloxycarbonyl groups, hexyloxycarbonyl groups, octyloxycarbonyl groups, decyloxycarbonyl groups, etc.

[0068] Examples of aryl groups with 6 to 30 carbon atoms include phenyl groups, naphthyl groups, anthranyl groups, pyrenyl groups, etc.

[0069] Examples of aralkyl groups (aryl alkyl groups) with 7 to 31 carbon atoms include benzyl groups and phenethyl groups (phenylethyl groups), and examples of aryloxy groups with 6 to 30 carbon atoms include phenyloxy groups (phenoxy groups), naphthyloxy groups, anthranyloxy groups, pyrenyloxy groups, etc.

[0070] Examples of aryloxycarbonyl groups with 7 to 31 carbon atoms include phenyloxycarbonyl groups, naphthyloxycarbonyl groups, anthranyloxycarbonyl groups, pyrenyloxycarbonyl groups, etc.

[0071] Examples of aralkyloxycarbonyl groups with 8 or more and 32 or fewer carbon atoms include benzyloxycarbonyl groups and phenethyloxycarbonyl groups.

[0072] Examples of acyl groups with 1 to 20 carbon atoms include the metanoyl group (formyl group), etanoyl group (acetyl group), propanoyl group, butanoyl group, pentanoyl group, hexanoyl group, octanoyl group, decanoyl group, benzoyl group, etc.

[0073] Examples of acyloxy groups with 1 to 20 carbon atoms include formyloxy, acetyloxy, propanoyloxy, butanoyloxy, pentanoyloxy, hexanoyloxy, octanoyloxy, decanoyloxy, and benzoyloxy.

[0074] In addition, the antifungal agent represented by the above chemical formula 1 is preferably at least one selected from the group consisting of compounds represented by the following chemical formulas 1-a to 1-c.

[0075]

[0076] In the above chemical formula 1, R 1 to R 3 It is a substituent composed of at least two types of atoms selected independently from the group consisting of carbon atoms, hydrogen atoms, and oxygen atoms.

[0077] Examples of substituents consisting of at least two atoms selected from the group consisting of carbon atoms, hydrogen atoms, and oxygen atoms are the same as those above, so they are omitted here.

[0078] More specific examples of compounds represented by the above chemical formula 1 include parahydroxybenzoic acid esters such as methyl parahydroxybenzoate (methyl parahydroxybenzoate), ethyl parahydroxybenzoate (ethyl parahydroxybenzoate), butyl parahydroxybenzoate (butyl parahydroxybenzoate), and benzyl parahydroxybenzoate (benzyl parahydroxybenzoate); Examples include salicylic acid, methyl salicylate, phenol, catechol, resorcinol, hydroquinone, isopropylphenol, cresol, thymol, phenoxyethanol, phenylphenol (2-phenylphenol, 3-phenylphenol, 4-phenylphenol, 2-phenylethyl alcohol (phenethyl alcohol)), etc. Among these, from the view that the desired effect of the present invention is more effectively exhibited, at least one compound represented by Chemical Formula 1 is preferably selected from the group consisting of ethyl parahydroxybenzoate, butyl parahydroxybenzoate, and phenylphenol, and butyl parahydroxybenzoate is more preferred.

[0079] Alternatively, the antifungal agent (preservative) may be an unsaturated fatty acid. Examples of unsaturated fatty acids include monounsaturated fatty acids such as crotonic acid, myristoleic acid, palmitoleic acid, oleic acid, and ricinoleic acid; diunsaturated fatty acids such as sorbic acid, linoleic acid, and eicosadienoic acid; triunsaturated fatty acids such as linolenic acid, pinolenic acid, and eleostearic acid; tetraunsaturated fatty acids such as stearidonic acid and arachidonic acid; pentaunsaturated fatty acids such as boseopentaenoic acid and eicosapentaenoic acid; and hexaunsaturated fatty acids such as docosahexaenoic acid and nisinic acid. Among these, sorbic acid is preferred as the unsaturated fatty acid from the viewpoint that the desired effect of the present invention is more effectively exhibited.

[0080] In addition to the above, 1,2-alkanediols such as 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol; alkylglyceryl ethers such as 2-ethylhexylglyceryl ether (ethylhexylglycerin); and compounds such as capric acid and dehydroacetic acid may be used as antifungal agents (preservatives).

[0081] The above antifungal agent (preservative) may be used alone or in combination of two or more types.

[0082] When a polishing composition includes an antifungal agent (preservative), the content (concentration) of the antifungal agent (preservative) in the polishing composition is not particularly limited. For example, in the case of a polishing composition used as a polishing liquid for polishing an object to be polished (typically a slurry-type polishing liquid, which may also be referred to as a working slurry or polishing slurry), the lower limit of the content (concentration) of the antifungal agent (preservative) in the polishing composition is preferably 0.0001 mass% or more, more preferably 0.001 mass% or more, and even more preferably 0.01 mass% or more. Furthermore, the upper limit of the content (concentration) of the antifungal agent (preservative) is preferably 3 mass% or less, and more preferably less than 1 mass%. That is, the content (concentration) of the antifungal agent (preservative) in the polishing composition is preferably 0.0001 mass% or more and 3 mass% or less, more preferably 0.001 mass% or more and 3 mass% or less, and even more preferably 0.01 mass% or more and less than 1 mass%. Within this range, a sufficient effect is obtained to inactivate or destroy microorganisms.

[0083] In addition, for a polishing composition (i.e., concentrate, raw material of working slurry) that is diluted and used for polishing, the content of the antifungal agent (preservative) is typically 10 mass% or less, and more preferably 5 mass% or less, from the perspective of improving polishing speed. In addition, from the perspective of reducing the burden of treating the polishing composition after use, i.e., waste liquid treatment, the content of the antifungal agent (preservative) is preferably 0.03 mass% or more, and more preferably 0.3 mass% or more.

[0084] In addition, if the polishing composition contains two or more types of antifungal agents (preservatives), the above content is intended to be the total amount thereof.

[0085] The dispersant is not particularly limited and can be appropriately selected according to the desired use or purpose. From the perspective of dispersibility after storage (particularly the dispersibility of zirconia particles), it is preferable to use sugar alcohols. The surface of zirconia particles (abrasives) is typically hydrophobic, and the abrasives tend to aggregate with each other. Furthermore, the polishing composition according to the present invention includes at least one salt consisting of a monovalent anion and a cation with one or more valences as a selectivity enhancer, thereby improving electrical conductivity (EC) and reducing the electrostatic repulsion between zirconia particles (abrasives), which makes the abrasives more prone to aggregation. When sugar alcohols are mixed with zirconia particles (abrasives), hydrophobic groups (hydrocarbon groups) of the sugar alcohols attach to the hydrophobic surface of the zirconia particles, and hydroxyl groups of the sugar alcohols are oriented toward the outside of the zirconia particles, thereby making the surface of the zirconia particles hydrophilic. Due to this hydrophilization, the zirconia particles become easily mixed with a dispersion medium (especially water) and can exist as separate particles. Additionally, sugar alcohols are attached to the surface of the particles, causing steric hindrance and suppressing aggregation between the particles. Furthermore, the mechanism for improving the dispersibility of the zirconia particles is speculative, and the present invention is not limited to such speculation.

[0086] That is, in one embodiment of the present invention, the polishing composition further comprises at least one dispersant selected from the group consisting of sugar alcohols.

[0087] Sugar alcohols are not particularly limited, but it is preferable that they have three or more hydroxyl groups in the molecule. Specifically, examples include pentaerythritol, dipentaerythritol, sorbitan, adonitol, maltitol, threitol, erythritol, arabinitol, ribitol, xylitol, iditol, sorbitol, mannitol, lactitol, galactitol, dulcitol, thallitol, alitol, perseitol, bollemitol, D-erythro-L-galoctitol, D-erythro-L-thaloctitol, erythromannoctitol, D-threo-L-galoctitol, D-arbo-D-mannononitol, D-gluco-D-galacdesitol, bornecitol, conduritol, inositol, ononitol, pinitol, pinpolitol, quebrachitol, valienol, biscumitol, etc. Among these, straight-chain sugar alcohols are more preferred, specifically xylitol, sorbitol, adonitol, threitol, erythritol, arabinitol, ribitol, iditol, mannitol, galactitol, thalitol, alitol, and perceitol are preferred, xylitol and sorbitol are more preferred, and sorbitol is even more preferred. These sugar alcohols can be used as a single type or in combination of two or more types.

[0088] The molecular weight of the sugar alcohol is not particularly limited, but it is preferably 80 or higher, more preferably 100 or higher, and even more preferably 120 or higher. Additionally, the molecular weight of the sugar alcohol is not particularly limited, but it is preferably less than 1000, more preferably 600 or lower, even more preferably 400 or lower, and particularly preferably 200 or lower. That is, the molecular weight of the sugar alcohol is preferably 80 or higher and less than 1000, more preferably 100 or higher and 600 or lower, more preferably 120 or higher and 400 or lower, and particularly preferably 120 or higher and 200 or lower.

[0089] In the case where the polishing composition of the present invention further comprises a dispersant (particularly a sugar alcohol), the content (concentration) of the dispersant (particularly a sugar alcohol) is not particularly limited and can be appropriately selected according to the desired use or purpose. For example, in a working slurry (polishing slurry), the content (concentration) of the dispersant (particularly a sugar alcohol) in the polishing composition is, for example, 10 ppm or more, preferably 50 ppm or more, more preferably 80 ppm or more, and even more preferably 90 ppm or more, with respect to the total mass of the polishing composition. In addition, the upper limit of the content (concentration) of the dispersant (particularly a sugar alcohol) in the polishing composition is, for example, 500 ppm or less, preferably 300 ppm or less, more preferably 200 ppm or less, and even more preferably less than 200 ppm, with respect to the total mass of the polishing composition. That is, the content (concentration) of the dispersant (especially sugar alcohol) in the polishing composition is, for example, 10 ppm or more and 500 ppm or less, preferably 50 ppm or more and 500 ppm or less, more preferably 80 ppm or more and 500 ppm or less, even more preferably 90 ppm or more and 300 ppm or less, particularly preferably 90 ppm or more and 200 ppm or less, and most preferably 90 ppm or more and less than 200 ppm, with respect to the total mass of the polishing composition. If the content of the dispersant is within this range, good dispersibility can be maintained even after the abrasive particles (especially zirconia particles) have been stored for a long period of time.

[0090] The polishing composition according to the present form may be a one-component type or a multi-component type including a two-component type. In addition, the polishing composition according to the present form may be prepared by diluting the stock solution of the polishing composition with a diluent such as water by, for example, 2 to 100 times, preferably 2 to 50 times, and more preferably 3 to 10 times on a volume basis.

[0091] [Method for manufacturing a polishing composition]

[0092] The method for preparing the abrasive composition according to the present form is not particularly limited and can be obtained, for example, by stirring and mixing abrasive particles, a selectivity enhancer, a pH adjuster, and optionally additives in a dispersion medium (preferably in water). The details of each component are as described above.

[0093] The temperature at which each component is mixed is not particularly limited, but it is preferably between 10°C and 40°C, and heating may be used to increase the dissolution rate. In addition, the mixing time is not particularly limited as long as uniform mixing is possible.

[0094] [Polishing method and semiconductor substrate manufacturing method]

[0095] The above polishing composition is suitable for use in polishing objects comprising SiOC and SiN. Accordingly, according to another embodiment of the present invention, a polishing method is provided comprising a process of polishing SiOC and SiN objects using the above polishing composition. Furthermore, according to another embodiment of the present invention, a method for manufacturing a semiconductor substrate is provided, comprising a process of polishing a semiconductor substrate comprising SiOC and SiN by the above polishing method.

[0096] As a polishing device, a general polishing device may be used, which is equipped with a holder that holds and supports a substrate having a workpiece to be polished, a motor capable of changing the rotational speed, and a polishing plate to which a polishing pad (polishing cloth) can be attached.

[0097] As a polishing pad, general nonwoven fabrics, polyurethane, porous fluoropolymers, etc., can be used without particular restrictions. It is preferable that the polishing pad be formed with grooves to collect the polishing liquid.

[0098] Regarding the grinding conditions, for example, the rotational speed of the grinding platen and carrier is 10 rpm (0.17 s -1 ) or more at 500 rpm (8.33 s-1 ) or less is preferable. The pressure applied to the substrate having the object to be polished (polishing pressure) is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa).

[0099] The method of supplying the polishing composition to the polishing pad is not particularly limited, and, for example, a method of continuous supply using a pump or the like is employed. Although there is no limit to the amount supplied, it is preferable that the surface of the polishing pad always be covered with the polishing composition according to the present invention.

[0100] After polishing is finished, the substrate is cleaned in an aqueous solution, and water droplets attached to the substrate are blown off by a spin dryer or the like, thereby drying the substrate to obtain a substrate having a layer containing SiOC and SiN.

[0101] Although embodiments of the present invention have been described in detail, it is clear that this is illustrative and exemplary and is not limiting, and that the scope of the present invention should be interpreted by the appended claims.

[0102] The present invention includes the following embodiments and forms.

[0103] 1. Abrasives comprising at least one type of zirconia particle, and

[0104] A selectivity ratio improver comprising at least one salt consisting of a monovalent anion and a cation of monovalent or higher, which improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, and

[0105] pH adjuster containing at least one type of acid

[0106] Includes,

[0107] The pH is greater than 3.0 and less than 7.0, and

[0108] A polishing composition in which the zeta potential of the above-mentioned abrasive particles is a positive value.

[0109] 2. A polishing composition described in 1. above, wherein the concentration of the selectivity enhancer is 50 ppm or more and 1000 ppm or less.

[0110] 3. A polishing composition described in 1. or 2. above, having a pH of 4.0 or higher and 6.0 or lower.

[0111] 4. The above pH adjuster is a polishing composition described in any one of 1 to 3, comprising acetic acid.

[0112] 5. The above selectivity enhancer is a polishing composition described in any one of 1 to 4, comprising ammonium acetate.

[0113] 6. A polishing composition as described in any one of 1 to 5, wherein the content of the abrasive particles is 0.01 mass% or more and 1.0 mass% or less.

[0114] 7. A polishing composition as described in any one of 1 to 6, further comprising at least one dispersant selected from the group consisting of sugar alcohols.

[0115] 8. A polishing method comprising a process of polishing a workpiece comprising SiOC and SiN using a polishing composition described in any one of 1 to 7 above.

[0116] 9. A method for manufacturing a semiconductor substrate having a process of polishing a semiconductor substrate including SiOC and SiN by the polishing method described in 8.

[0117] [Example]

[0118] The present invention will be explained in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Also, unless otherwise noted, “%” and “parts” mean “mass%” and “mass parts,” respectively.

[0119] [Methods for Measuring Various Physical Properties]

[0120] In this embodiment, various physical properties were measured by the following method.

[0121] <Measurement of particle diameter (D50)>

[0122] The value of D50 of the zirconia particles was adopted as the value measured as the volume-averaged particle diameter by the dynamic light scattering method using a particle diameter distribution measuring device (Nanotrack UPA-UT151, manufactured by Microtrack Bell). More specifically, the particle diameter of the zirconia particles was measured using a dispersion solution in which the zirconia particles were dispersed in water. By analysis using the measuring instrument, the particle diameter (D50) was calculated from the particle diameter distribution of the zirconia particles, at which the accumulated particle volume on the fine particle side reached 50% of the total particle volume.

[0123] Measurement of Zeta Potential

[0124] The zeta potential of the zirconia particles was measured using a zeta potential measuring device manufactured by Malvern Panalytical (product name "Zettasizer Nano ZSP").

[0125] <pH의 측정>

[0126] The pH of the polishing composition was measured using a pH meter (manufactured by Horiba Seisakusho Co., Ltd., Model No.: F-71).

[0127] [Preparation of abrasive composition]

[0128] (Example 1)

[0129] Colloidal zirconia (manufactured by Dai-ichi Kigenso Kagaku Kogyo Co., Ltd., ZSL-20N (ZrO2 sol, D50: 70 nm)) was added to pure water, the dispersion medium, at room temperature (25 °C) to a final concentration of 0.10 mass% as abrasive particles, and ammonium acetate was added to a final concentration of 50 ppm as a selectivity enhancer. Additionally, BIT (1,2-benzisothiazol-3(2H)-one, manufactured by Sanai Sekiyu Co., Ltd.) was added as an antifungal agent to a final concentration of 0.3 g / kg (0.03 mass%) to obtain a mixture. Acetic acid was added to the obtained mixture as a pH adjuster to achieve a pH of 5.0, and the mixture was stirred and mixed at room temperature (25 °C) for 30 minutes to prepare a polishing composition. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 It was mV. In addition, the particle diameter of the colloidal zirconia in the polishing composition was the same as the particle diameter of the colloidal zirconia.

[0130] (Example 2)

[0131] A polishing composition was prepared in the same manner as in Example 1, except that ammonium acetate was added to pure water to a final concentration of 100 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0132] (Example 3)

[0133] A polishing composition was prepared in the same manner as in Example 1, except that ammonium acetate was added to pure water to a final concentration of 200 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0134] (Example 4)

[0135] A polishing composition was prepared in the same manner as in Example 1, except that ammonium acetate was added to pure water to a final concentration of 500 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0136] (Example 5)

[0137] A polishing composition was prepared in the same manner as in Example 1, except that ammonium acetate was added to pure water to a final concentration of 1000 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0138] (Example 6)

[0139] A polishing composition was prepared in the same manner as in Example 4, except that acetic acid was added to the mixture to make the pH 4.0. The zeta potential of the colloidal zirconia in the obtained polishing composition was +37 mV.

[0140] (Example 7)

[0141] A polishing composition was prepared in the same manner as in Example 4, except that acetic acid was added to the mixture to make the pH 4.5. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0142] (Example 8)

[0143] A polishing composition was prepared in the same manner as in Example 4, except that acetic acid was added to the mixture to make the pH 6.0. The zeta potential of the colloidal zirconia in the obtained polishing composition was +30 mV.

[0144] (Example 9)

[0145] A polishing composition was prepared in the same manner as in Example 4, except that ammonium nitrate was used as a selectivity enhancer instead of ammonium acetate and nitric acid was used as a pH adjuster instead of acetic acid. The zeta potential of the colloidal zirconia in the obtained polishing composition was +36 mV.

[0146] (Example 10)

[0147] A polishing composition was prepared in the same manner as in Example 4, except that nitric acid was used as a pH adjuster instead of acetic acid. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0148] (Example 11)

[0149] A polishing composition was prepared in the same manner as in Example 4, except that potassium acetate was used as a selectivity enhancer instead of ammonium acetate. The zeta potential of the colloidal zirconia in the obtained polishing composition was +36 mV.

[0150] (Example 12)

[0151] Colloidal zirconia (manufactured by Dai-ichi Kigenso Chemical Engineering Co., Ltd., ZSL-20N (ZrO2 sol, D50: 70 nm)) was added to pure water, a dispersion medium, at room temperature (25 ℃) to a final concentration of 0.10 mass% as abrasive particles, ammonium acetate to a final concentration of 500 ppm as a selectivity enhancer, and sorbitol to a final concentration of 10 ppm as a dispersant. Additionally, BIT (1,2-benzisothiazol-3(2H)-one, manufactured by Sanai Sekiyu Co., Ltd.) was added as an antifungal agent to a final concentration of 0.3 g / kg (0.03 mass%) to obtain a mixture. Acetic acid was added to the obtained mixture as a pH adjuster to achieve a pH of 5.0, and the mixture was stirred and mixed at room temperature (25 ℃) for 30 minutes to prepare a polishing composition. The obtained polishing composition The zeta potential of the colloidal zirconia in the composition was +35 mV. In addition, the particle diameter of the colloidal zirconia in the polishing composition was the same as the particle diameter of the colloidal zirconia.

[0152] (Example 13)

[0153] A polishing composition was prepared in the same manner as in Example 12, except that sorbitol was added to pure water to a final concentration of 50 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0154] (Example 14)

[0155] A polishing composition was prepared in the same manner as in Example 12, except that sorbitol was added to pure water to a final concentration of 80 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0156] (Example 15)

[0157] A polishing composition was prepared in the same manner as in Example 12, except that sorbitol was added to pure water to a final concentration of 100 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0158] (Example 16)

[0159] A polishing composition was prepared in the same manner as in Example 12, except that sorbitol was added to pure water to a final concentration of 200 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0160] (Example 17)

[0161] A polishing composition was prepared in the same manner as in Example 12, except that sorbitol was added to pure water to a final concentration of 500 ppm. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0162] (Example 18)

[0163] A polishing composition was prepared in the same manner as in Example 15, except that xylitol was used as a dispersant instead of sorbitol. The zeta potential of the colloidal zirconia in the obtained polishing composition was +35 mV.

[0164] (Comparative Example 1)

[0165] A polishing composition was prepared in the same manner as in Example 1, except that no selectivity enhancer was added and nitric acid was used as a pH adjuster instead of acetic acid. The zeta potential of the colloidal zirconia in the obtained polishing composition was +34 mV.

[0166] (Comparative Example 2)

[0167] A polishing composition was prepared in the same manner as in Example 1, except that a selectivity enhancer was not added. The zeta potential of the colloidal zirconia in the obtained polishing composition was +36 mV.

[0168] (Comparative Example 3)

[0169] A polishing composition was prepared in the same manner as in Example 4, except that ammonium oxalate monohydrate was used instead of ammonium acetate. The zeta potential of the colloidal zirconia in the obtained polishing composition was -32 mV.

[0170] (Comparative Example 4)

[0171] A polishing composition was prepared in the same manner as in Example 4, except that tri-ammonium citrate was used instead of ammonium acetate. The zeta potential of the colloidal zirconia in the obtained polishing composition was -39 mV.

[0172] (Comparative Example 5)

[0173] A polishing composition was prepared in the same manner as in Example 4, except that acetic acid was added to the mixture to make the pH 3.0. The zeta potential of the colloidal zirconia in the obtained polishing composition was +39 mV.

[0174] (Comparative Example 6)

[0175] A polishing composition was prepared in the same manner as in Example 4, except that acetic acid was added to the mixture to make the pH 7.0. The zeta potential of the colloidal zirconia in the obtained polishing composition could not be measured because the colloidal zirconia had aggregated.

[0176] (Comparative Example 7)

[0177] A polishing composition was prepared in the same manner as in Example 4, except that acetic acid was added to the mixture to make the pH 8.0. The zeta potential of the colloidal zirconia in the obtained polishing composition could not be measured because the colloidal zirconia had aggregated.

[0178] (Comparative Example 8)

[0179] A polishing composition was prepared in the same manner as in Example 4, except that colloidal zirconia (manufactured by Daiichiki Genso Kagaku Kogyo Co., Ltd., ZSL00014 (ZrO2 sol), D50: 15 nm) was added to pure water as abrasive particles in place of colloidal zirconia (ZSL-20N) to achieve a final concentration of 1.0 mass%. The zeta potential of the colloidal zirconia in the obtained polishing composition was -23 mV.

[0180] (Comparative Example 9)

[0181] A polishing composition was prepared in the same manner as Comparative Example 1, except that colloidal silica (D50: 70 nm) with amino groups immobilized on its surface was used as abrasive particles instead of colloidal zirconia (ZSL-20N). The zeta potential of the colloidal silica in the obtained polishing composition was +24 mV.

[0182] (Comparative Example 10)

[0183] A polishing composition was prepared in the same manner as Comparative Example 1, except that colloidal ceria (D50: 70 nm) was used as abrasive particles instead of colloidal zirconia (ZSL-20N). The zeta potential of the colloidal ceria in the obtained polishing composition was +33 mV.

[0184] (Comparative Example 11)

[0185] A polishing composition was prepared in the same manner as Comparative Example 1, except that colloidal alumina (D50: 300 nm) was used as abrasive particles instead of colloidal zirconia (ZSL-20N). The zeta potential of the colloidal alumina in the obtained polishing composition was +29 mV.

[0186] [Grinding Speed]

[0187] As polishing targets (substrates), a 300 mm wafer (SiOC film, manufactured by Advance Material Technology Co., Ltd., product name: BD2x 5kA Blanket) and a 300 mm wafer (SiN (silicon nitride film), manufactured by Advance Material Technology Co., Ltd., product name: LP-SiN 3.5KA Blanket) were prepared.

[0188] Using the polishing composition obtained above, the prepared substrate was polished under each of the following polishing conditions, and the polishing rate was measured:

[0189] (Grinding conditions)

[0190] Grinder: EJ-380IN-CH (Manufactured by Nihon Engisu Co., Ltd.)

[0191] Polishing pad: Hard polyurethane pad (Manufactured by Nitta DuPont Co., Ltd., IC1010)

[0192] Grinding pressure: 3.0 psi (1 psi = 6894.76 Pa)

[0193] Platen rotation speed: 60 rpm

[0194] Head (Carrier) Rotation Speed: 60 rpm

[0195] Flow rate of abrasive composition: 100 ml / min

[0196] Polishing time: 30 seconds.

[0197] (Grinding speed)

[0198] The film thickness was determined by an optical interference film thickness measuring device (manufactured by SCREEN Holdings Co., Ltd., model number: Lambda Ace VM-2030), and the polishing speed was evaluated by dividing the difference in film thickness before and after polishing by the polishing time (see formula below). The polishing speed of SiOC is preferably 1700 Å / min or higher, and the polishing speed of SiN is preferably less than 30 Å / min.

[0199]

[0200] (Selection Ratio)

[0201] The selectivity ratio was calculated by dividing the polishing rate of the SiOC substrate obtained above by the polishing rate of the SiN substrate. It is preferable that the selectivity ratio be 100 or higher.

[0202] [Storage Stability]

[0203] The average secondary particle diameter (D50) of the abrasive particles in each abrasive composition was measured at room temperature (25 ℃) by the dynamic light scattering method using a particle diameter distribution measuring device (Nanotrack UPA-UT151, manufactured by Microtrack Bell). Specifically, by analysis using the measuring instrument, the particle diameter D50 (nm) was calculated from the particle size distribution of the abrasive particles, at which the integrated particle volume on the fine particle side reaches 50% of the total particle volume, and this was used to define the average secondary particle diameter (D50) of the abrasive particles. A )(nm) is used.

[0204] Separately, each polishing composition (100 g) was weighed using a poly bottle. Subsequently, each poly bottle was placed in a constant temperature bath set to 80 ℃ and left for two weeks. After leaving for a predetermined period, the average secondary particle size (D50) of the abrasive particles in each polishing composition B)(nm) is measured in the same way as above.

[0205] Average secondary particle size of abrasives before and after storage (average secondary particle size of abrasives before storage (D50) A (nm)) and average secondary particle size of abrasives after storage (D50 B Based on (nm), the growth rate (%) of the average secondary particle size was calculated according to the following formula and used as an indicator of storage stability. Storage stability (growth rate of average secondary particle size) (%) indicates that the smaller the absolute value, the better the storage stability. The absolute value of storage stability (growth rate of average secondary particle size) (%) is acceptable if it is 40% or less, preferably 35% or less, more preferably 25% or less, even more preferably less than 10%, and particularly preferably less than 5%.

[0206]

[0207] The evaluation results of the polishing compositions of each example and each comparative example are shown in Table 1 below. In addition, “-” in Table 1 indicates that the formulation was not used.

[0208]

[0209] As shown in Table 1, it can be seen that the polishing composition of the example can polish SiOC at a high polishing speed while keeping the polishing speed of SiN low, thereby improving the ratio (selectivity ratio) of the polishing speed of SiOC to the polishing speed of SiN.

[0210] This application is based on Japanese Patent Application No. 2022-35214 filed on March 8, 2022 and Japanese Patent Application No. 2022-145042 filed on September 13, 2022, the disclosures of which are incorporated by reference in their entirety.

Claims

Claim 1 A polishing composition comprising abrasive particles comprising at least one type of zirconia particle, a selectivity ratio improver comprising at least one salt composed of a monovalent anion and a monovalent or higher cation that improves the ratio of the polishing rate of SiOC to the polishing rate of SiN, and a pH adjuster comprising at least one type of acid, wherein the pH is greater than 3.0 and less than 7.0, and the zeta potential of the abrasive particles is a positive value. Claim 2 A polishing composition according to claim 1, wherein the concentration of the selectivity enhancer is 50 ppm or more and 1000 ppm or less. Claim 3 A polishing composition according to claim 1, wherein the pH is 4.0 or higher and 6.0 or lower. Claim 4 A polishing composition according to claim 1, wherein the pH adjuster comprises acetic acid. Claim 5 A polishing composition according to claim 1, wherein the selectivity enhancer comprises ammonium acetate. Claim 6 A polishing composition according to claim 1, wherein the content of the abrasive particles is 0.01 mass% or more and 1.0 mass% or less. Claim 7 A polishing composition according to claim 1, further comprising at least one dispersant selected from the group consisting of sugar alcohols. Claim 8 A polishing method comprising a process of polishing a workpiece containing SiOC and SiN using a polishing composition described in any one of claims 1 to 7. Claim 9 A method for manufacturing a semiconductor substrate having a process of polishing a semiconductor substrate including SiOC and SiN by the polishing method described in claim 8.

Citation Information

Patent Citations

  • Polishing composition, polishing method and manufacturing method of ceramic component

    JP2016124047A

  • Polishing composition and method for using abrasive particles treated using aminosilane

    JP2017135387A

  • Polishing liquid, polishing liquid set, and substrate polishing method

    JP2017139349A

  • Abrasive grain, manufacturing method therefor, polishing slurry containing the same, and polishing method using the same

    JP2019203088A

  • Polishing method for low-K substrates

    JP2019508880A